Sistem Informasi Manejemen Keuangan Harian Berbasis Web Pada Warung Nasi Rames - Hibatullah Dzaky Ikram Hakim; Bima Ardiansyah Haz; Mifdzal Azriel; Afiani Agus Abdillah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The primary challenge currently faced by Warung Nasi Rames is its daily bookkeeping method, which still relies on manual paper-based recording. This conventional practice frequently leads to lost records, mathematical calculation errors, and difficulties in tracking cash flow. To address these issues, a web-based financial management information system has been successfully developed. The system's development utilizes XAMPP as the local server, integrated with PHP scripting and a MySQL database for data management. Furthermore, the design process is based on a descriptive analysis approach involving field observations, direct interviews, and literature reviews. The core features provided include menu data management, daily income and expense recording, and the instant generation of profit and loss statements. System testing demonstrates a significant increase in efficiency regarding data recap speed and calculation accuracy, owing to the minimization of manual intervention (human error). In conclusion, this digitalization facilitates the owner in evaluating daily profitability while ensuring that cash flow is systematically recorded, thereby supporting better-informed business decisions.